1977
DOI: 10.1029/rs012i001p00141
|View full text |Cite
|
Sign up to set email alerts
|

On auroral electrojet curvature and the interpretation of azimuth‐scan, radar Doppler data

Abstract: In this paper we show that the geometrical configuration of the auroral electrojet is of great importance in the interpretation of Doppler velocity data obtained by auroral backscatter radars operated close to the auroral oval at low elevation angles. We show that some of the characteristic features in the azimuthal dependence of the radar Doppler velocity can be explained by accounting for the auroral electrojet curvature produced by (1) the shape of the auroral oval, (2) the altitude variation of the Hall an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1977
1977
1992
1992

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…They found that these observations could be accounted for qualitatively by considering the rotation of the current direction with height (due to the height dependence of the Hall and Pedersen conductivities). Brekke et al [1977] have noted that the curvature of the auroral electrojet must be considered when treating this effect qualitatively. Abel and Newell [1969] also examined how the magnitude of the Doppler velocity depended on height.…”
Section: Introductionmentioning
confidence: 99%
“…They found that these observations could be accounted for qualitatively by considering the rotation of the current direction with height (due to the height dependence of the Hall and Pedersen conductivities). Brekke et al [1977] have noted that the curvature of the auroral electrojet must be considered when treating this effect qualitatively. Abel and Newell [1969] also examined how the magnitude of the Doppler velocity depended on height.…”
Section: Introductionmentioning
confidence: 99%
“…For a sufficiently large area we may then take independent 1-o-s velocity measurements along two or more different directions from a single radar site and combine them to yield the two-dimensional velocity vector, provided that the velocity is constant over the common ionospheric volume. This arrangement is illustrated in The radar analysis techniques assuming L shell invariance that axe described below axe entirely consistent with the analysis approach advocated by Brekke et al [1977] and differ from the constant range azimuth scan analysis which they criticized. In the present analyses, a flow along an L shell does not exhibit any curvature relative to the locus of radar measurements.…”
Section: Single-station Radarsmentioning
confidence: 61%
“…Our analysis shows that velocity estimates made using single-station radars under the assumption of any fixed form of spatial uniformity (e.g., L shell invariance) axe subject to substantial errors due to a violation of this uniformity by natural spatial variations that must be present in any realistic global convection pattern, as well as in smaller-scale flow structures associated with magnetospheric phenomena of high scientific interest, such as the ionospheric manifestations of flux transfer events [Lee, 1986;Southwood, 1987] and pressure pulses [Southwood and Kivelson, 1990]. In fact, the bidirectional data sampling modes of single-station incoherent scatter radars, such as the ElSCAT CP-4 or "Polar" modes and the Sondrestrom 13-position scan, cannot test for the spatial uniformity of the convection, and, in contrast to the expectations of Brekke et al [1977], even the multidirectional scan of the Goose Bay and Halley PACE raaars is insensitive to large-scale spatial variations in the convection which can compromise the velocity determination. Most importantly, it is not possible to determine from the data alone those vector determinations that are compromised and those that axe not.…”
Section: Paper Number 91ja00445mentioning
confidence: 99%
See 2 more Smart Citations